Determining Technological Innovation and Competitiveness: A Cross Organizational Analysis of the Malaysian Manufacturing Industry - Ibrahim, Amlus; Mohamed Elias, Ezanee; Saad, Abd.Rahim; Ramayah, T. (School of Business and Management Institut Teknologi Bandung, 2008)
This study analyzed the determinants of technological innovation in the Malaysian manufacturing industry. Its main purpose is to identify a set of management- related variables characterizing Malaysian innovative firms. Moreover, the study aimed to test whether the set of determinant differs for firms with different technological trajectories. A sample of 204 Malaysian firms was used for the investigation, with one respondent from each firm. The questionnaire measured the technological innovation, as well as 5 main potential determinants of innovation adopted from literature. Statistical analysis used, including bivariate correlation and multivariate regression, in identifying association between the technological innovation and the determining variables. The results of the analysis lead the researcher to the model of 5 important determining factors of technological innovation. The important factors were intensity of R&D, trvhnoogical trajectories,intensity of marketing, engineers, scientist and managers with experience locally and technical competency of personnel,. The analysis of technological trajectories confirmed the hypotheses that set of important determinants of innovation as well as the extent of technological innovation differs for firms in different innovation processes.Keywords: Technologies trajectories, technological innovation, intensity of R&D.